Stakeholder Perceptions of Landscape Justice in the Case of Atlantic Salmon Fishing in Northern Finland - Landauer, Mia; Joona, Juha; Keskitalo, Pigga (Land, 2023)
Atlantic salmon fishing in northern Fennoscandia is part of controversial ecological, sociocultural, legal, and political questions. This paper presents a study of landscape justice as perceived by stakeholders who practice, manage, and govern traditional, household, and recreational salmon fishing on northern Finland’s border rivers, Tornio (Torne) and Teno (Tana). The concept of landscape justice is analysed through the lens of distributive, substantive, procedural, and recognition forms of justice. The data are based on semi-structured stakeholder interviews (N = 15). A qualitative content analysis of the data based on the forms of justice reveals that salmon are associated with diverse environmental, economic, and sociocultural values of the landscape. The study results show the current state governance mode of salmon fishing causes landscape injustice manifesting, in particular, as an unequal distribution of risks and benefits regarding fishing governance and its challenges. There is unclear legislation for Tornio. Landscape justice is violated by regulations causing unclear case law for Teno on the ownership of land or water and related fishing restrictions, as well as a lack of possibilities for local tourist entrepreneurs and household fishermen to participate in decision making. Governmental decisions are mainly based on the overall ecological status of salmon populations at the expense of local variations or the recognition and systemic evaluation of sociocultural and local economic values of the landscape. The results indicate a need for national and cross-border policy decisions to include sociocultural and economic aspects of Atlantic salmon fishing to guide movement towards more just environmental governance.